2016
DOI: 10.1007/s13203-016-0147-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature oxidative asphaltenes liquefaction for petrochemicals: fact or fiction?

Abstract: Asphaltene is the heavy and heteroatom-rich fraction of petroleum that is rejected during a solvent deasphalting process. In patent literature there are claims that state that this material can be converted into an aromatic petrochemical feedstock by oxidative liquefaction at low temperature. To evaluate the validity of these claims, asphaltenes from an industrial solvent deasphalting process were oxidized with dry and water-saturated air at temperatures in the range 45-100°C. Infrared spectroscopy of the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Depending on the origin, asphaltenes can have around 10 18 spins•g −1 free radicals, which can promote reactions during oxygen chemisorption, favoring the interactions over different points in the asphaltene molecular structure. 62 However, for all cases, the pressure increase favors the amount of chemisorbed oxygen in the n-C 7 asphaltene structure due to the thermal expansion of the aggregates, increasing the number of active sites available for the interaction with oxygen atoms. 27 Although the oxygen content follows another order, a direct relationship with oxygen in the form of carboxyl groups in the molecular structure of the system was found.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Depending on the origin, asphaltenes can have around 10 18 spins•g −1 free radicals, which can promote reactions during oxygen chemisorption, favoring the interactions over different points in the asphaltene molecular structure. 62 However, for all cases, the pressure increase favors the amount of chemisorbed oxygen in the n-C 7 asphaltene structure due to the thermal expansion of the aggregates, increasing the number of active sites available for the interaction with oxygen atoms. 27 Although the oxygen content follows another order, a direct relationship with oxygen in the form of carboxyl groups in the molecular structure of the system was found.…”
Section: Resultsmentioning
confidence: 96%
“…62 A possible pathway for ester formation is explained in Scheme 1, where oxidation of cycloalkanes as proposed by Klerk et al is shown. 62 Because asphaltenes are rich in multicycle molecules where cycloalkane and aromatic rings are adjoining, indan hydroperoxide functions as a good representative of a substructure obtained in the complex molecules. 62 The suggested pathway begins with the formation of an oxygen-centered alkoxy radical from indan, which can produce alcohol by taking out hydrogen from another hydrocarbon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations